Business law and commercial law in Malaysia - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2025)
The book Business and Commercial Law consists of 29 chapters capturing the above two important areas of laws by discussing the specific subject matter from each of the above subjects from the Malaysian perspective. It encompasses an introduction to law and Legal Systems with special features of Malaysian laws and the courts, the essentials of the law of contracts and law of torts and the various business entities such as sole proprietorship, partnership, and corporations. The book also covers the law relating to Agency, Franchise, Competition, Bailment, Banking and Digital Banking, and essentials of Islamic Banking. Further, the laws relating to Immovable Property, Consumer protection, Revenue law, Employment law, Sale of Goods, Hire-Purchase, Insurance law, Cyber law, Intellectual Property and Trade Secrets, Insolvency and E-commerce laws are also included as specific chapters and discussed with reference to the law and practice in Malaysia. The additional featured of this book are chapters relating to Anti-Money Laundering, Anti-Terrorism Financing, Commercial Crimes, International Trade Law, International Investment Law, and the Settlement of Commercial Disputes. All in all, this book is an excellent source of reference as it is an all-embracing manuscript on the business and commercial law contributed by a pool of academics who are extensively involved in the research and publication on this subject. This book will be a precious source of reference and be immensely beneficial to a wide range of readers, and an essential reading for students pursuing Business Law and/or Commercial Law.